2023
DOI: 10.3389/fimmu.2023.1091941
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatics design of multivalent epitope vaccine against monkeypox virus and its variants using membrane-bound, enveloped, and extracellular proteins as targets

Abstract: IntroductionThe current monkeypox (MPX) outbreak, caused by the monkeypox virus (MPXV), has turned into a global concern, with over 59,000 infection cases and 23 deaths worldwide.ObjectivesHerein, we aimed to exploit robust immunoinformatics approach, targeting membrane-bound, enveloped, and extracellular proteins of MPXV to formulate a chimeric antigen. Such a strategy could similarly be applied for identifying immunodominant epitopes and designing multi-epitope vaccine ensembles in other pathogens responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 107 publications
(128 reference statements)
1
16
0
Order By: Relevance
“…Although some other studies also focused on designing an immunoinformatics-based vaccine against MPXV, the proteins utilized in these studies are different from the protein used in this study. ,, In a similar study, the EEV Type-I membrane glycoprotein was used, but the predicted epitopes are different to those predicted in this study . Similarly, another study predicted the epitope “FSIGGVIHL” and used it for the formulation of the vaccine against MPXV; however, our designed vaccine binds more strongly with the human toll-like receptors as compared to the vaccine designed in that study .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although some other studies also focused on designing an immunoinformatics-based vaccine against MPXV, the proteins utilized in these studies are different from the protein used in this study. ,, In a similar study, the EEV Type-I membrane glycoprotein was used, but the predicted epitopes are different to those predicted in this study . Similarly, another study predicted the epitope “FSIGGVIHL” and used it for the formulation of the vaccine against MPXV; however, our designed vaccine binds more strongly with the human toll-like receptors as compared to the vaccine designed in that study .…”
Section: Discussionmentioning
confidence: 92%
“…68,90,91 In a similar study, the EEV Type-I membrane glycoprotein was used, but the predicted epitopes are different to those predicted in this study. 91 Similarly, another study predicted the epitope "FSIGGVIHL" and used it for the formulation of the vaccine against MPXV; however, our designed vaccine binds more strongly with the human toll-like receptors as compared to the vaccine designed in that study. 68 Furthermore, the vaccine designed in this study is effective for individuals worldwide because the epitopes of vaccine covered 100% of the world population.…”
Section: Discussionmentioning
confidence: 99%
“…Waqas et al . (2023) assembled the best B- and T-cell epitopes obtained from A35R, A43R, B16R, B21R, C4L, E8L, E13L, E21R, and G10R proteins into a vaccine construct and used RpfE sequence as an adjuvant to boost vaccine immunogenicity [ 102 ]. In the study by Zaib et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to population coverage analysis, the vaccine construct covers 95.57% of the worldwide population, while the vaccine designed in study of Waqas et al . covers 93.62% of the worldwide population [ 102 ]. The high antigenicity scores predicted by the VaxiJen 2.0 server and the ANTIGENpro server showed that the proposed vaccine is effective enough to elicit strong immune responses in the body.…”
Section: Discussionmentioning
confidence: 99%
“…12 In this immunologic environment, the further possibility that the multi-epitope vaccines can trigger an exacerbation of inflammatory skin disease in genetically predisposed patients. 13 Interestingly, the relapse of autoimmune conditions as psoriasis and AD could be related to the aberrant activation of the Tissueresident memory (TRM) T cells, a newly identified subset of memory T cells originating from the differentiation of naive T cells in the skin following antigen exposure. TRM cells persist long-term in tissues without recirculating in the blood thus providing a first line of adaptive cellular defense.…”
Section: Dear Editormentioning
confidence: 99%